2010
DOI: 10.1242/jeb.037002
|View full text |Cite
|
Sign up to set email alerts
|

Allometry of hummingbird lifting performance

Abstract: SUMMARYVertical lifting performance in 67 hummingbird species was studied across a 4000m elevational gradient. We used the technique of asymptotic load-lifting to elicit maximum sustained muscle power output during loaded hovering flight. Our analysis incorporated direct measurements of maximum sustained load and simultaneous wingbeat kinematics, together with aerodynamic estimates of mass-specific mechanical power output, all within a robust phylogenetic framework for the Trochilidae. We evaluated key statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(101 citation statements)
references
References 48 publications
5
95
1
Order By: Relevance
“…>10°C; see Figs S1 and S4). For hummingbirds, interspecific comparisons indicate that heavier species tend to be found at higher elevations (Altshuler et al, 2004(Altshuler et al, , 2010. A similar pattern of body mass increase characterizes Andean passerines and ducks across elevation (Blackburn and Ruggiero, 2001;Gutiérrez-Pinto et al, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…>10°C; see Figs S1 and S4). For hummingbirds, interspecific comparisons indicate that heavier species tend to be found at higher elevations (Altshuler et al, 2004(Altshuler et al, , 2010. A similar pattern of body mass increase characterizes Andean passerines and ducks across elevation (Blackburn and Ruggiero, 2001;Gutiérrez-Pinto et al, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…The induced power P ind , corresponding to the energy rate required to generate vertical force, was calculated using an estimated total system mass of (m b þ m water þ [F feather /g]), where m b is the body mass and g is the acceleration owing to gravity (figure 1). Profile power P pro , corresponding to the energy rate required to overcome form and skin drag of the wings, was calculated assuming simple harmonic motion and a drag coefficient of 0.139 [15]. The profile drag coefficient was assumed to be constant for both dry and wet conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, a careful comparative study of the scaling of pectoralis mass and wing planform indicates that mass-specific power available from the flight muscles of hummingbirds scales slightly negatively with increasing mass, but not as negatively as wingbeat frequency. Hummingbirds exhibit compensatory scaling of wing dimensions and muscle mass [25,30]. Partial compensatory mechanisms are reported for positive scaling of proportions of glycolytic fibre types in the pectoralis of woodpeckers [93] and pectoralis strain in a variety of bird species ranging in size from hummingbirds to Galliform birds ( [23,96]; figure 3).…”
Section: Scaling Of Flight Performance (A) On Being Largementioning
confidence: 99%
“…(b) On being small: hovering Hummingbirds are the smallest birds, with species varying in mass from 2-12 g and a large outlier, the giant hummingbird, having a mass of 20 g [25,30]. One hypothesis meriting further study in relation to the observed positive scaling of load-lifting ability with increasing mass in hummingbirds [25] is that the smallest hummingbirds may have evolved into a morphospace where available time for muscle contraction is functioning as a constraint upon muscle force production [14,96,97].…”
Section: Scaling Of Flight Performance (A) On Being Largementioning
confidence: 99%